Addressing the impacts of waste on overall project performance: a study of applying lean construction principle in Public Works Department (PWB), Bangladesh - Uddin, Abid Moin (BRAC University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.